Peningkatan kualitas biofertilizer Kasgot menggunakan Pichia cecembensis UNJCC Y-157 dan asam amino untuk meningkatkan pertumbuhan tanaman sawi hijau (Brassica juncea L.) - Ariskaa, Riska; Surono; Sukmawati, Dahlia (Innovation Centre for Tropical Sciences, 2024)
Mustard greens (Brassica juncea L.) is a crop with relatively high productivity due to its abundant soil nutritional content. Soil fertility enhancement is commonly achieved through fertilization. Kasgot fertilizer, a biofertilizer derived from the residue of black soldier fly (BSF, Hermetia illucens) larvae that consume fermented feed, serves as an eco-friendly option beneficial for plant growth. This organic waste is fermented with microorganisms, specifically the yeast Pichia cecembensis UNJCC Y-157, provided by the Jakarta State University, along with added amino acids. This study aimed to determine the effects of P. cecembensis UNJCC Y-157 yeast and amino acids on BSF larval growth and to assess the impact of the resulting kasgot fertilizer on mustard greens growth. This research used a completely randomized design (CRD) with three treatments, including one control, with five replications on fermented BSF larvae feed. For the application of kasgot fertilizer on mustard greens, four treatments with four replications were applied, with data analyzed using one-way analysis of variance (ANOVA). The results indicated that BSF larvae fed with added P. cecembensis UNJCC Y-157 yeast and amino acids had superior wet weight, observed through morphological characteristics. Additionally, in terms of mustard greens growth, parameters such as plant height, leaf count, leaf width, leaf length, and fresh weight showed that kasgot fertilizer containing P. cecembensis UNJCC Y-157 yeast yielded better than morphological outcomes in the plants. Keywords: Pichia cecembensis, fermented feed, black soldier fly, Brassica juncea L., amino acids